Energizing Slow Scholarship: A Political Ecology Approach to a More Just Academy and Beyond - Martin, Patricia M.; Nevins, Joseph (ACME, 2024)
The term “slow scholarship” has become increasingly prominent in academia in recent years. It is an analytical framework for critiquing the neoliberalization and corporatization of the academy, and the associated “speeding up” of academic labor. The phrase also serves as a call to transform institutions of higher education so that they are more responsive to the needs of academic workers and the students whom they serve. For proponents of slow scholarship, such a transformation necessitates a stretching out of time, a slowing down, to allow for enhanced reflection and inquiry. Missing thus far from the discussion of slow scholarship is how energy, particularly of a fossil-fueled variety, facilitates the speed-up of the academy. Indeed, the “fast” academy requires high levels of energy consumption. Employing a political ecology lens, we thus seek to enlarge the scope of slow scholarship, while pushing for a broader and deeper political project. We contend that a more expansive slow scholarship requires grappling with energy consumption and mobility as well as their associated inequities. This entails, as we explore in the conclusion, a project of justice that transcends the boundaries of the academy. Such a project involves “stretching the boundaries of care” to recognize, include and transform the human and non-human assemblages that help make contemporary academia possible.